Professional Development Practices Readiness Level among Design and Technology Subject Teachers in SJKC Primary Schools Selangor - Chong, Way Lim; Abdul Rahman, Khairul Anuar (Research and Innovation in Technical and Vocational Education and Training, 2024)
This study aims to identify the Level of Teacher Readiness and Professional Development Practices of SJKC Primary Schools in Selangor towards Design & Technology. The level of preparedness studied is knowledge, skills, attitudes, interpersonal relationships, and workload. The study is a descriptive survey involving quantitative data using a questionnaire as a research instrument. The sample of respondents was 97 people taken from the entire population. The data collected from the questionnaire was analyzed using Statistical Package For Science School (SPSS) software version 26 in a descriptive manner which involved calculating frequency, percentage, and mean to identify the level of readiness for aspects of knowledge, skills attitudes, and professional development practices of teachers. The descriptive data obtained shows an overall mean value for the readiness level variable of 3.27 which is at a moderate level and the professional development practice variable of 3.43 which is also at a high level. Then, this finding was used to conduct the Kruskal-Wallis test and found that there was a difference between the level of readiness of RBT teachers towards the professional development practices of SJKC primary school teachers in Selangor. Next, these findings are used to conduct inferential statistical analysis. The researcher has used Spearman's Rank Correlation test for this purpose. Based on the test, the correlation value is as much as 0.78 which means that the two variables have a strong positive correlation. In conclusion, this finding shows that the level of readiness of SJKC primary school RBT teachers has a strong relationship with the professional development practices of teachers in their respective SJKC primary schools.